Exploration of mitochondrial defects in sarcopenic hip fracture patients. Issue 10 (October 2022) - Hintze, Stefan; Baber, Lisa; Hofmeister, Fabian; Jarmusch, Stefanie; Todorow, Vanessa; Mehaffey, Stefan; Tanganelli, Fabiana; Ferrari, Uta; Neuerburg, Carl; Teupser, Daniel; Bidlingmaier, Martin; Marques, Jair Gonzalez; et al.
Abstract: Severe cases of age-related loss of muscle function and mass are clinically unique to sarcopenia. Mitochondrial dysfunction has been associated with aging and sarcopenia, but the causal connection in this context is not well eluded. Here we investigated different aspects of mitochondrial respiration in sarcopenia. Open muscle biopsies were taken from a total of 31 hip fracture patients, older than 70 years. Patients were assigned a sarcopenia Z-score based on EWGSOP2 criteria. Primary myoblast cultures were generated from the muscle tissue samples and used for real time metabolic measurement. Muscle and serum samples showed correlation of high Z-scores with reduced mitochondrial complex I activity, increased tricarboxylic acid cycle (TCA) metabolites, reduced vitamin D3 levels, and signs of an altered iron metabolism. Primary myoblast cultures gained from the same muscle biopsies did not show significant mitochondrial defects. We hypothesize that a sum of external consequences, including vitamin D3 deficiency and iron deficiency caused by disturbances in the iron metabolism, result in complex I deficiency, which in turn affects the TCA and contributes to muscle weakness and loss. Abstract : Sarcopenia; Tricarboxylic acid cycle; TCA; Mitochondria; Metabolism; Myoblast culture.